Sleep and Daytime Complaints During Manic and Depressive Episodes in Children and Adolescents With Bipolar Disorder - Lopes, Maria Cecilia; Boarati, Miguel Angelo; Fu-I, Lee (Frontiers in Psychiatry, 2020)
Introduction Depressive and manic episodes of bipolar disorder can interact with sleep complaints, followed by a worsened psychiatric condition. The aim of this study was to examine the interaction of sleep disorders with bipolar disorder in youths during depressive and manic episodes. Methods The target population was children and adolescents drawn from the Children and Adolescents Affective Disorder Program. Clinical assessment for current psychiatric diagnosis was done by direct clinical interview, Diagnostic Interview for Children and Adolescents (DSM-IV), and best-estimated clinical consensus. We applied sleep questionnaires from which we obtained sleep and daytime complaints during manic and depressive episodes. All statistical tests of significance were done using 2-tailed tests with α = 0.05. Results Participants in this study comprised 29 children (age = 10 ± 3 years, boys = 23) and 43 adolescents (age = 15 ± 2.4 years, boys = 30). Sleep complaints were observed in 66.4% of participants during manic episodes and 52.3% during depressive episodes. 37.9% of patients had sleep complaints in both episodes. Time in bed was longer during depressive episodes than manic episodes (p = 0.01). We found a high prevalence of nocturnal enuresis in depressive episodes in children and adolescents, which was statistically significant compared with manic episodes (p < 0.05). Unrested sleep was higher in adolescents in both episodes, and it was statistically significant during manic episodes (p < 0.05). Conclusion According to our analyses, the minority of patients had sleep complaints in both episodes. Our data showed that nocturnal enuresis occurred more frequently during depressive than manic episodes. Further research is necessary to understand the implications of these data.